DOSE RESPONSE ON THE TESTING OF 137CESIUM PANORAMIC IRRADIATION DEVICE PROTOTYPE FOR PERSONNEL DOSIMETER - Eko Budi Jumpeno; Ismanto Jumadi; Rofiq Syaifudin; Yogi Ferdiansyah; Eka Aulia Ardyanti (Badan Standardisasi Nasional, 2023)
The dosimetry laboratory has to ensure that the implementation of quality assurance of testing meets clause 7.7 of the SNI ISO/ IEC17025: 2017. One of the activities to meet the quality assurance is to irradiate the personnel dosimeter at radiation facility that is traced to national or international standard. In this research it has been outlined the dose response of personnel on the prototype of the 137Cs panoramic irradiation device and its dose rate distribution. It was prepared 40 dosimeters for each of OSLD and TLD-900 which were divided into 5 groups. Each group consists of 8 dosimeters with 6 dosimeters for irradiated and 2 dosimeters as control. The dosimeter were mounted on the holders of 137Cs panoramic irradiation device prototype and exposed with irradiation time of 7.3 minutes, 54.5 minutes, 165 minutes, 330 minutes and 545.2 minutes respectively. Then they were evaluated using the OSLD microStar Reader or the TLD reader. Meanwhile, RaySafe Xi survey with its detector was prepared to measure dose rate in the holder 1 to 6 for 5 minutes. The study showed that the reading dose of TLD-900 were relatively higher than OSLD. The difference of TLD-900 reading dose to OSLD ranged from 0.10 – 1.44 mSv with a greater tendency for the higher dose. The linearity curve between reading dose to exposure time tends to be linear with a correlation factor (R2) of 0.9999 for OSLD and 0.9988 for TLD-900. The linearity equation on OSLD is y = 0.0184x – 0.0326. While the linearity equation for TLD-900 is y = 0.0214x – 0.1201. The dose rate on the holder 1 to 6 has an average of 1.02 mSv/h with the standard deviation of 1.5%. The dose rate distribution at a distance of 29 cm from the source ranges from 1.01 - 1.04 mSv/jam.